Hermeneutika Pembaharuan Pendidikan Islam di Indonesia (Aplikasi Teori Hermeneutika Hasan Hanafi dalam Pemikiran Abdul Wahid Hasyim Tentang Pendidikan Islam di Indonesia) - Muhammad Muslih; Angga Nuraufa Zamzami Saputra; Wahyu Lailatul Baridah (Tim Jurnal STAI KH. Zainuddin Ponpes Mojosari, 2024)
Hermeneutics in general can be said to be a method of understanding not only texts, but thoughts, including Indonesian Islamic educational thought. With this method, the significance of educational thinking that has great potential to be developed today will be seen. In this case, Hasan Hanafi's hermeneutical reading begins with the essence of Wahid Hasyim's educational thought and its influence on the historical conditions surrounding it in decision making; second, exploration of Wahid Hasyim's educational reform methods as outlined in eidetic criticism; third, what are the moral values that want to be built practically in the Islamic education system in Indonesia based on the presuppositions and horizons of Indonesian society which are the targets of its educational thinking.